Peningkatan Hasil Belajar Matematika Dengan Menggunakan Pendekatan Realistic Mathematic Education (RME) Siswa Sekolah Dasar - Tatang Jaka; Mufarizuddin Mufarizuddin; Nurmalina Nurmalina (LPPI Yayasan Almahmudi bin Dahlan, 2023)
This research was motivated by the low learning outcomes of students in mathematics subjects in class IV SDN 013 Ganting, Salo District, Kampar Regency. One solution to overcome this problem is to use the RME approach. The aim of this research is to describe the improvement in mathematics learning outcomes on multiples and number factors using the RME approach for fourth grade students at SDN 013 Ganting. This research method is Classroom Action Research (PTK) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation, reflection and research time carried out from March to August 2017. The research subjects were 11 class IV students, with 6 male students and 6 female students. totaling 5 people. Collection techniques include documentation, observation and tests. The results of this research can be concluded that the student learning outcomes for class IV fractions at SDN 013 Ganting in cycle I were classified as good with an average of 77.27. Furthermore, of the 11 students who completed it, only 8 students completed it, while classical learning completion was 72.73%. In cycle II it was very good with an average of 84.09 and 11 students, there were 9 students who completed it while classical learning completeness was 81.82%. Thus, it can be concluded that using the Realistic Mathematic Education (RME) approach can improve mathematics learning outcomes in multiples and number factors for class IV SDN 013 Ganting. Keywords: Learning Outcomes, Mathematics, Realistic Mathematic Education